Green house gas mitigation potential in dairy production systems - Baltenweck, Isabelle; Fraval, Simon; Rao, E.J.O; Githinji, Julius; Githoro, Edmund; Atieno, Turry (International Livestock Research Institute, 2024)
Estimating green house gas mitigation potential in dairy production systems and assessing the feasibility of carbon market linkages.